Evaluation of Clinicopathological Features and Associated Conditions in Erythema Annulare Centrifugum: A Retrospective Observational Analysis of 63 Patients - Funda Erduran (Mattioli1885, 2024)
Introduction: Erythema annulare centrifugum (EAC) is a rare reactive disease that typically presents as annular or polycyclic erythematous lesions. There are few studies about EAC in the literature; therefore, data on the pathogenesis of the disease are limited. Objectives: We aimed to examine the demographic, clinical, pathological characteristics and associated conditions of the patients with EAC. Methods: We analyzed records of the patients with EAC who admitted to our clinic in the last four years retrospectively. Results: A total of 63 patients, 39 women and 24 men, were included in our study. The mean age of the patients was 47.8±11.2 years. The mean disease duration was 15.54±12 months. The trunk and thigh were the most commonly involved sites (49%, 33%). Associated conditions were identified in 52.3% of the patients. Infections (N = 16), malignancies (N = 6), rheumatic diseases (n=4) and drugs (n=4) were the most common precipitating factors respectively. The most common infections were superficial fungal infections and Helicobacter pylori infection. Histopathologically, 10 patients had deep type and 53 patients had superficial type EAC. We determined that the disease duration from the onset of the disease was longer (12.3 versus 16.2 months) and the number of attacks (1.2 versus 2.8 attacks) was higher in the superficial type when compared to the deep type (P = 0.042, P = 0.038). Conclusions: In our study, infections, malignancies and rheumatic diseases were among the most common etiologic factors. We would also like to draw attention to Helicobacter pylori infection as a precipitating factor which may be a novel finding.